The Influence of the Faith-Islam-Ikhsan Concept on Attitudes and Actions in the Face of Ecological Disasters - Amalia, Sukmah; Lumintang, Aji; Pradipta, Reyhan Zhafar; Hidayatullah, Ahmad Fauzan (FALASIFA : Jurnal Studi Keislaman, 2024)
This study aims to explore the influence of the concepts of faith, Islam, and ikhsan on individual attitudes and actions in the face of ecological disasters. The research method used is qualitative and quantitative analysis of primary and secondary data. The results showed that the concept of faith provides a strong moral foundation for individuals to act proactively in the face of ecological disasters. In addition, Islamic principles provide in-depth ethical guidance in safeguarding the natural environment. The concept of ikhsan, which refers to perfection in worship, also plays a role in shaping the attitude of individuals who care about the environment. The implication of these findings is the need for the integration of religious values in efforts to mitigate and adapt to ecological disasters in order to create a more environmentally conscious and responsible society.